COSMOGENIC RADIONUCLIDES FROM FIORD LANDSCAPES SUPPORT DIFFERENTIAL EROSION BY OVERRIDING ICE SHEETS - Briner J.P.; Miller G.H.; Davis P.T.; Finkel R.C. (My University, 2006)
The interpretation of differentially weathered mountainous areas along the fringes of Pleistocene ice sheets is fundamental for determining ice-sheet behavior and thickness during the last glaciation. Two existing interpretations are either that highly weathered uplands remained as nunataks while freshly eroded troughs held outlet glaciers during the last glaciation or that uplands and lowlands were equally covered by ice, but that it was differentially erosive as a function of its spatially variable basal thermal regime. Cosmogenic radionuclide measurements from 33 bedrock samples and 27 upland erratics from differentially weathered fiord landscapes on northeastern Baffin Island shed light on Laurentide Ice Sheet (LIS) dynamics and thickness. Tors on weathered upland surfaces have minimum 10Be ages between ca. 50 and ca. 170 ka (n = 12), whereas the majority of erratics perched in the uplands range from ca. 10 to ca. 13 ka (n = 14), indicating that the whole landscape was glaciated during the Last Glacial Maximum (LGM). Glacially sculpted bedrock (n = 7) near sea level reflects the age of deglaciation, and increasing amounts of isotopic inheritance in high-elevation sculpted bedrock (n = 3), higher elevation intermediately weathered bedrock (n = 11), and highest elevation intensely weathered bedrock reflect the weakening of erosive power as the ice sheet transitioned from fiords to interfiord plateaus. Cold-based glaciation of uplands was contemporaneous with warm-based glaciation in fiords, suggesting the presence of ice streams, 26Al and 10Be concentrations measured in 10 bedrock samples indicate that tors have experienced a complex history of alternating periods of exposures, burial, and limited glacial erosion. The paired isotope data reveal a minimum duration of burial of 80-500 k.y., presumably by cold-based ice, and indicate that the tors have an age of at least 150-580 ka. These data, together with other reconstructions of ice streams in the eastern Canadian Arctic, suggest that ice streams were a large influence on northeastern LIS dynamics throughout the late Quaternary. Thus, the northeastern LIS was sensitively tied with North Atlantic thermohaline circulation and abrupt climate change. © 2006 Geological Society of America.
Keywords: BASAL THERMAL REGIME; COSMOGENIC RADIONUCLIDE; FJORD; GLACIER EROSION; LAURENTIDE ICE SHEET; WEATHERING ZONE; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен